1989
DOI: 10.1002/macp.1989.021900815
|View full text |Cite
|
Sign up to set email alerts
|

Poly(alkylene phosphate)s by polycondensation of phosphonic diamides with diols

Abstract: Polycondensation of diols with phosphonic bis(dialky1amide)s leads to high-molecular-weight polyphosphites (a, up to 4 . lo4). Model reactions of 1-butanol, 2-butanol and phenol with phosphonic bis(diethy1amide) (1) were studied and it was established, that these reactions exhibit characteristic induction periods. Linearization of the kinetic curves after addition of amines prior to reaction enabled us to postulate the mechanism of esterification, involving activation of 1 by hydrogen-bonding to amines. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…On the other hand, the first PPE with high molecular weight was prepared more than 20 years ago by using ROP. 8,9,20,[23][24][25][26]33,[56][57][58][59][60][61][62][63][64][65] The initial attempts to prepare high molecular weight polyphosphonates esters by the transesterification method were unsuccessful. 8,9,20,[23][24][25][26]33,[56][57][58][59][60][61][62][63][64][65] The initial attempts to prepare high molecular weight polyphosphonates esters by the transesterification method were unsuccessful.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, the first PPE with high molecular weight was prepared more than 20 years ago by using ROP. 8,9,20,[23][24][25][26]33,[56][57][58][59][60][61][62][63][64][65] The initial attempts to prepare high molecular weight polyphosphonates esters by the transesterification method were unsuccessful. 8,9,20,[23][24][25][26]33,[56][57][58][59][60][61][62][63][64][65] The initial attempts to prepare high molecular weight polyphosphonates esters by the transesterification method were unsuccessful.…”
Section: Discussionmentioning
confidence: 99%
“…In the last 30 years, a variety of different polyphosphonates and polyphosphate esters have been produced 8,9,20,[23][24][25][26]33,[56][57][58][59][60][61][62][63][64][65] and transesterification is one of the most important method used in the field. This transesterification method described by Myrex et al 56 showed several advantages.…”
Section: Transesterificationmentioning
confidence: 99%
See 2 more Smart Citations
“…They have studied extensively the synthesis of these polymers, obtained by various routes, such as ring-opening polymerization (ROP), polycondensation, and polyaddition. [4][5][6][7] Since the 1980s, several groups, representatives including Leong's and Zhuo's groups, have explored the biomedical applications of PPEs, initially for controlled drug delivery. [8][9][10][11][12][13][14][15] Since the late 1990s, taking advantage of the versatility of the PPE's pendant groups, they have conjugated various groups to PPEs for gene delivery and tissue engineering applications.…”
Section: Introductionmentioning
confidence: 99%